2021
DOI: 10.1101/2021.09.08.458725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The vacuolar iron transporter mediates iron detoxification inToxoplasma gondii

Abstract: Iron is essential to living cells, acting as a cofactor in a number of essential enzymes in metabolism; however, iron requires proper storage or it can be dangerous to the cell. In both yeast and plants, iron is stored in a vacuole through the action of a vacuolar iron transporter (VIT). This transporter is conserved in the apicomplexan family of obligate intracellular parasites, including in Toxoplasma gondii, a pathogen of medical and veterinary importance. Here, we assess the role of VIT in T. gondii. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…gondii [ 32 ], and modulation of intracellular iron levels is critical for the survival of T . gondii parasites [ 33 ]. Directly linking iron metabolism in the parasite and ETC activity through the Fe-S clusters of Tg ApiCox13 provides these parasites with a means of regulating the ETC (and associated processes such as ATP synthesis and pyrimidine synthesis) in response to iron availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gondii [ 32 ], and modulation of intracellular iron levels is critical for the survival of T . gondii parasites [ 33 ]. Directly linking iron metabolism in the parasite and ETC activity through the Fe-S clusters of Tg ApiCox13 provides these parasites with a means of regulating the ETC (and associated processes such as ATP synthesis and pyrimidine synthesis) in response to iron availability.…”
Section: Discussionmentioning
confidence: 99%
“…Given that loss of its Fe-S clusters led to decreased Complex IV stability and activity, we speculate that TgApiCox13 has a role in the iron-dependent regulation of ETC function. Iron is an important micronutrient for many intracellular parasites, including T. gondii [32], and modulation of intracellular iron levels is critical for the survival of T. gondii parasites [33]. Directly linking iron metabolism in the parasite and ETC activity through the Fe-S clusters of TgApiCox13 provides these parasites with a means of regulating the ETC (and associated processes such as ATP synthesis and pyrimidine synthesis) in response to iron availability.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…A Vacuolar Iron Transporter (VIT) was recently characterized and found to localize to a vesicular compartment that partially colocalized with TgCPL (Aghabi et al, 2021). The study found that the VIT was important for detoxification of excess iron and for parasite virulence (Aghabi et al, 2021).…”
Section: Functions Of the Plvacmentioning
confidence: 99%